Análisis multitemporal del uso del suelo en el páramo de la comunidad Salamalag Chico, parroquia Guangaje, provincia de Cotopaxi 2014-2022 - Ramírez Luje, Joselyn Fernanda (2023)
The aim of the research project was to analyze the land use changes in the páramo of Salamalag Chico community, parish of Guangaje, province of Cotopaxi during the period 2014-2022. The Corine Land Cover methodology adopted in Ecuador was applied considering the protocol and guidelines established by the MAE, MAGAP, and National Secretariat of Planning and Development for the classification of vegetation cover and land use of Continental Ecuador, we worked with Landsat 8 satellite images, the thematic classes were identified through the supervised classification in which an agricultural database obtained from the geo portal of Agro Ecuatoriano was interposed, seven classes were identified: páramo, livecstock area, cereal crops, vegetable crops, leguminous crops, tuber crops, and the eroded area, the data obtained were validated using the confusion matrix and kappa index. With the multitemporal analysis, we generate two transition matrices to show the changes in land use during the analysis periods. The results indicated predominance in páramo: 2014 (1231.74 ha; 49.25%); 2018 (1092.27 ha; 43.71%); 2022 (1125.3 ha; 45.76%). The multitemporal analysis showed that in the period 2014-.2018, one of the most significant changes is the loss of the páramo due to the intensification of tuber crops with an extension of 114.20 ha, while in 2022 there were changes of tuber crops to páramo areas where recovery of 87.85 ha was observed, due to the fact that farmers stopped cultivating certain areas in such a way that the páramo managed to recover. We may infer that the páramo has changed over time, with the loss in the first four years of the analysis due to an increase in anthropogenic activity being more obvious, and the páramo recovering in the year 2022, which was accomplished with the assistance of the community.